Tree cover is crucial but riparian areas provide a strategic focus for preserving an urban avoider in a fragmented urban ecosystem. (1st October 2020) - Connelly, Christine A.; Lennox, Erin; Isaac, Bronwyn; Aulich, Vincent; Cooke, Raylene; Weston, Michael A.; White, John G.
ABSTRACT: Local native species that decline in response to urbanisation are often classified as 'urban avoiders'. Their decline drives the biotic homogenisation seen in cities but the characterisation of these species as urban avoiders may discourage efforts to conserve them in urban landscapes. We used gradient analysis and species distribution modelling to examine habitat availability and fragmentation along an entire urban-forest gradient for a representative urban avoider – the Eastern Yellow Robin ( Eopsaltria australis ). Gradient analysis had utility in quantifying threats for this species but species distribution modelling better highlighted conservation opportunities in the landscape. The amount of suitable habitat declined with increasing urbanisation whilst fragmentation increased. Towards the city centre, habitat clustered around major waterways. Riparian networks showed clear potential to facilitate the restoration of connectivity between urban and fringing habitat and we identify 'missing links' in this network – key opportunities for habitat restoration. Riparian vegetation escapes development, is the preferred habitat for many species, including humans, and can serve as the logical architecture on which to focus conservation efforts. Restoring habitat along riparian networks in cities can build comprehensive and fully connected biotic infrastructure that facilitates human-nature connections and conserves local native species diversity.